Tamm Review: Nutrient cycling in forests: A historical look and newer developments - Johnson, Dale W.; Turner, John (Forest ecology and management, 2019)
•Some components of forest nutrient cycles are measured others are calculated.•Reliable estimates of soil weathering, N fixation, and nutrient export remain elusive.•Nutrient cycling depictions do not include the effects of catastrophic events.•Predictions from these traditional models have had mixed results.•New information requires revision of traditional models. In this review, we consider a traditional conceptual model of nutrient cycling in forests and evaluate (1) assumptions and issues with existing methods for measuring and calculating nutrient pools and fluxes, including the estimation of errors; (2) how various elements of the conceptual model vary with geographic and climatic region, and gaps in knowledge about certain regions; (3) predictions from nutrient cycling data for the effects of harvesting, burning, fertilization, and elevated CO2, including the effects of nutrient cycling on productivity and the effects of productivity on nutrient cycling. As is true of all models, traditional models of forest nutrient cycling are all incorrect in the sense that they are approximations and do not capture all features the real world. For example, none of these traditional models include the important effects of catastrophic events such as wildfire, insect attack, hurricanes, etc. Nonetheless, traditional nutrient cycling models have allowed us to explore the collective implications of our current understanding of nutrient cycling processes. While the methods apply to plantations the focus of this review has been on natural forest studies. Despite much effort, reliable estimates of some transfers such as soil weathering and nitrogen fixation remain elusive. Soluble exports on a watershed level are not reliable representatives of exports from terrestrial nutrient cycles because correct conditions for such measurements are relatively rare and also because such estimates are subject to deep soil weathering and stream spiraling beyond the rooting zone. Soluble exports by lysimetery are subject to errors in the estimation of water flux and the delineation of the depth of rooting. The current versions of these traditional models will no doubt require modifications in the future to account for new information becomes available, for example, the delays between root uptake and the appearance of nutrients in aboveground biomass, the importance of soil nutrient hotpots for uptake, and the unforeseen ability of nitrogen-limited trees to extract additional nitrogen from soils when root growth in stimulated by elevated CO2.